1953
DOI: 10.3181/00379727-82-20087
|View full text |Cite
|
Sign up to set email alerts
|

An Activator System in Blood Indispensable for Formation of Plasmin by Streptokinase.

Abstract: The fibrinolytic agent produced by certain stone(2) showed that in addition to the strepstreptococci (streptokinase) was originally tococcal factor, a "lytic factor" in serum was thought to be a iibrinolytic enzyme( 1 ). Mil-necessary for the production of fibrinolysis.Later, Christensen ( 3 ) found that plasmino-* Preliminary Communication: The 2nd Internagen, a precursor in blood, was transformed to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

1956
1956
1971
1971

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(36 citation statements)
references
References 0 publications
2
32
0
2
Order By: Relevance
“…It is evident that the two distinct activities of plasminogen preparations developed under the influence of streptokinase, the proteolytic and the activator activities, are differently related to the streptokinase concentrations employed. Whereas, proteolytic activity reaches a plateau at 100 streptokinase units per ml., which is maintained with 9 There is still controversy as to whether proactivator is an entirely separate substance or is derived from plasminogen itself (22,23,24), but the term is used to designate a plasma factor capable of reacting with streptokinase to form plasminogen activator. Though divergent emphasis has been placed on the significance of proactivator in the human as apart from the bovine system (25,26,27) for descriptive purposes we acknowledge its separate existence and assay for its biochemical activity even though its individual identity apart from plasminogen or its derivatives has not been clearly established.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that the two distinct activities of plasminogen preparations developed under the influence of streptokinase, the proteolytic and the activator activities, are differently related to the streptokinase concentrations employed. Whereas, proteolytic activity reaches a plateau at 100 streptokinase units per ml., which is maintained with 9 There is still controversy as to whether proactivator is an entirely separate substance or is derived from plasminogen itself (22,23,24), but the term is used to designate a plasma factor capable of reacting with streptokinase to form plasminogen activator. Though divergent emphasis has been placed on the significance of proactivator in the human as apart from the bovine system (25,26,27) for descriptive purposes we acknowledge its separate existence and assay for its biochemical activity even though its individual identity apart from plasminogen or its derivatives has not been clearly established.…”
Section: Resultsmentioning
confidence: 99%
“…This fact has prevented the useful estimation of the plasminogen, in animal sera and thus hampered study of the lysing system in experimental animals. With the appearance of the report that a mixture of human euglobulin and streptokinase results in a potent activator of certain animal sera (20), it seemed that its action might be sufficiently rapid to give complete activation of animal plasminogens.…”
Section: Guinea Pig Plasminogenmentioning
confidence: 99%
“…Fibrin digestion is the favorite method for determination of plasmin and dots for this purpose are commonly formed from animal fibrinogen that is only partially purified. A number of workers have shown that these dots are contaminated with plasminogen from their animal source (20,31). Consequently, lysis may be induced not only by the plasmin of the sample under test, but also by plasmin activated from the dot.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Profibrinolysin, tested by mixture of streptokinase and fractions in a bovine thrombin-fibrinogen clot, was present in tubes 5 to 16. As it might be argued that this test was actually measuring the presence of a streptokinase sensitive activator system (16) …”
Section: Baso4 Plasmamentioning
confidence: 99%